La pluralité des fonctions dévolues à la pneumatologie en théologie contemporaine: Appréciation critique et prospective, à partir des recherches d'Y.-M. Congar - Humann, François-Marie (Recherches de science religieuse, 2025)
Contemporary Trinitarian theology has placed in its centre the very person of Jesus Christ, as He who reveals to us the Father and gives us the Holy Spirit. What might be seen today as self-evident is nonetheless the fruit of important work markedly characteristic of theology in the second half of the 20th century. Congar is a significant witness to this, most especially in his attempt to conceive the place of the Holy Spirit in Christology. Although critical of the classical theology of the Incarnate Word, his proposal nevertheless does not make it out-dated. Rereading Congar shows us how very necessary is the articulation of he articles of faith among themselves (especially Incarnation, Pneumatology and Trinity). It is within this articulation that dogmatic theology asserts one of the major forms of its rationality.